Normal Adult Tympanogram Profile at H. Adam Malik Hospital in Medan - Meiza Ningsih (Pre Cure, 2014)
Aim: to know the timpanometric values in normal adults at the H.Adam Malik General Hospital Medan.Method: the study design was a descriptive research. This study obtained 142 people (284 ears) who meet the inclusion criteria. Data collection was done through physical examination of the ear with otoscope and hearing assessment with timpanometer.Result: The results showed from 142 sampel (284 ears) were found mean Vea 0,9672 cm3 with standard deviation 0,254, mean Peak Ytm : 0,533 (mmhos) with standard deviation 0,244 and mean Tw : 56 (daPa) with the standard deviation 16,63.Conclusion and Recommendation: The current study suggest normal adults may reguire gender, age and ras values when implementating a quantitative approach in tympanogram interpretation.